CONSUMER MEANINGS OF EVERYDAY FOOD ON INSTAGRAM THROUGH THE LENS OF SOCIAL REPRESENTATION THEORY: A REFLECTIVE THEMATIC ANALYSIS - Andi Sagita; Tanti Novianti; Zenal Asikin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study examines how consumers construct the social meanings of everyday food on Instagram using tilapia (Oreochromis sp.) consumption as an empirical context. Drawing on Social Representation Theory (SRT), the study interprets how shared meanings are built, negotiated, and objectified through visual and narrative representations in digital spaces. From more than 71,000 public posts tagged with #ikannila (tilapia fish), #nilamerah (red tilapia), and #nilahitam (black tilapia), a purposive sample of 391 selected consumer posts (2020–2024) was analysed using Reflective Thematic Analysis (RTA). Data validity was strengthened through thematic saturation and limited member checking. The analysis identified five main themes: Family, Flexibility, Taste, Locality, and Nutrition, which together form a structure of social meaning that reflects the emotional, practical, cultural, hedonic, and normative dimensions of everyday food consumption. The findings show that food functions not merely as a culinary object but as a cultural symbol that represents consumers' experiences and values. The implications of this study open opportunities for designing more resonant marketing messages as a foundation for meaning-driven marketing, using social representations of food to develop digital communication that is more authentic and participatory.